2010
DOI: 10.1124/jpet.110.171892
|View full text |Cite
|
Sign up to set email alerts
|

RG3487, a Novel Nicotinic α7 Receptor Partial Agonist, Improves Cognition and Sensorimotor Gating in Rodents

Abstract: Neuronal nicotinic ␣7 acetylcholine receptors (␣7nAChRs) are expressed primarily in the brain and are implicated in modulating many cognitive functions (e.g., attention, working and episodic memory). Not surprisingly, much effort has been committed to the development of molecules acting at ␣7nAChRs as potential therapies for a variety of central nervous system diseases (e.g., Alzheimer's). N-[(3S)-1-azabicyclo[2.2.2]oct-3-yl]-1H-indazole-3-carboxamide hydrochloride (RG3487) binds potently to the human ␣7nAChR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 39 publications
6
89
0
Order By: Relevance
“…More recently, the partial a 7 nAChR agonist SSR180711 was shown to reverse NMDAR antagonistinduced impairments in latent inhibition and novelty discrimination, two other gating and attentional tasks, and these effects were blocked by a 7 nAChR antagonists (Barak et al, 2009). Similar to the effects of mAChR activators, a 7 nAChR agonists have been shown to reverse the apomorphine-induced disruption of PPI (Hauser et al, 2009;Roncarati et al, 2009;Wallace et al, 2011).…”
Section: Preclinical Studies Of Full and Partial A 7 Nachr Agonistsmentioning
confidence: 85%
See 1 more Smart Citation
“…More recently, the partial a 7 nAChR agonist SSR180711 was shown to reverse NMDAR antagonistinduced impairments in latent inhibition and novelty discrimination, two other gating and attentional tasks, and these effects were blocked by a 7 nAChR antagonists (Barak et al, 2009). Similar to the effects of mAChR activators, a 7 nAChR agonists have been shown to reverse the apomorphine-induced disruption of PPI (Hauser et al, 2009;Roncarati et al, 2009;Wallace et al, 2011).…”
Section: Preclinical Studies Of Full and Partial A 7 Nachr Agonistsmentioning
confidence: 85%
“…In contrast to the lack of studies with muscarinic activators in preclinical models of NMDAR hypofunction, a 7 nAChR agonists such as SSR180711 produced robust efficacy in reversing both acute and chronic NMDAR antagonist-induced deficits in hippocampal and non-hippocampal memory tasks, including object recognition, Morris water maze, and Y-maze in rodents (Wishka et al, 2006;Boess et al, 2007;Pichat et al, 2007;Hashimoto et al, 2008;Thomsen et al, 2009). More recently, the partial a 7 nAChR agonist MEM3454 was also reported to reverse the chronic PCP-induced impairments of extradimensional attentional set-shifting in rats (Wallace et al, 2011). The effects of SSR180711 and MEM3454 in these NMDAR disruption models were blocked by a 7 nAChR antagonists (Pichat et al, 2007;Wallace et al, 2011;Thomsen et al, 2009).…”
Section: Neuropsychopharmacology Reviews Activation In Vivomentioning
confidence: 96%
“…On the other hand, reduced activity of either of these two receptors causes cognitive deficits in this paradigm (Boess et al, 2007;Curzon et al, 2006;Morris, 2006;Wallace et al, 2011). More generally, treatment of experimental animals with glutamate receptor antagonists impairs performance in a variety of cognitive tasks (Ahlander et al, 1999;Hauber and Schmidt, 1989;Karasawa et al, 2008;Venable and Kelly, 1990), whereas endogenous or exogenous glutamate receptor agonists promote cognitive performance (Clem et al, 2008;Lynch et al, 2008;Singer et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of a7nAChRs, like activation of NMDARs, increases the performance of experimental animals in the MWM (Duffy et al, 2008;Meyer et al, 1997;Riekkinen and Riekkinen, 1997;Timmermann et al, 2007;Wallace et al, 2011), a task that is extensively used to test hippocampusdependent spatial navigation and reference memory in rodents. On the other hand, reduced activity of either of these two receptors causes cognitive deficits in this paradigm (Boess et al, 2007;Curzon et al, 2006;Morris, 2006;Wallace et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that drugs activating muscarinic or nicotinic acetylcholine receptor (nAChR) subtypes have potential for the treatment of cognitive symptoms in patients with schizophrenia (for review, see Jones et al, 2012). Specifically, nicotine, as well as agonists and positive allosteric modulators of a7 and a4b2 nAChRs, attenuate various cognitive deficits in rodent models of schizophrenia (Boess et al, 2007;Hashimoto et al, 2008;Hauser et al, 2009;Hurst et al, 2005;Pichat et al, 2007;Rushforth et al, 2011;Thomsen et al, 2009;Timmermann et al, 2007;Wallace et al, 2011;Wildeboer and Stevens, 2008;Wishka et al, 2006). Our observations that nicotine reverses the selective CMOR impairment in rats treated with subchronic NMDAR antagonists is consistent with studies using standard object recognition tasks and extends these findings by implicating nAChRs in the potential treatment of multisensory integration deficits in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%